US Stadium Sitings: Communities Aren’t Yet Winning - Miriam Solis; C. Aujean Lee (Findings, 2025)
At the turn of the 21st century, urban economic development literature established that public subsidies for stadiums yielded few economic returns for localities, even when part of urban renewal initiatives. In our study of stadium sitings from 2000 to 2022, we find that stadiums are more geographically dispersed across regions and their relocations are largely intra-metropolitan. Stadiums sitings also continue to benefit from public subsidies, face little organized contestation, and there are very few instances of community-sharing agreements. Findings illustrate the ongoing need to specify how communities materially benefit from stadium development.